Peran Bauran Pemasaran Yang Mempengaruhi Peningkatan Pangsa Pasar Pada BUMDES - Feti Fatimah; Mega Anjar Widyabakti; Mohammad Faesal Sodikin (Universitas Muhammadiyah Jember, 2021)
Market share is used to analyze the target market of a product. To analyze the level of market share using the level of behavior of consumer purchasing decisions. Consumer purchasing decisions influenced by products, prices, promotions and distributions are a marketing mix. The objective to be achieved from the research is to analyze the relationship of products, prices, promotions and locations on the behavior of consumer purchasing decisions against BUMDes Karya Mandiri Balung Kulon Village. As well as to determine the strategy of increasing market share in BUMDes Karya Mandiri Balung Kulon Village. This research is associative research, which is research that connects more than one variable. Samples are technically non Random Sampling, namely purposive sampling. There are positive and significant influences among products, prices, locations, promotions on partial purchase decisions. This shows that if BUMDes produce a good product for consumers, it can determine prices that are able to compete, have a location that is easy to reach consumers, and promotions that can influence consumers will increase purchasing decisions. Input strategies that can be done BUMDes to increase market share is to develop product quality, increase product variations, set prices that are able to compete and innovate products.